Co může přinést studium oligomerizace proteinů v procesu onkogeneze? - Coufalová, D; Vojtěšek, B; Hernychová, L (Klinicka onkologie, 2015)
Many cellular proteins form oligomers. The equilibrium between monomeric and oligomeric states of these proteins is important for the regulation of protein activity. Modulation of the oligomerization equilibrium could be an interesting approach in the development of new therapeutic agents. This review summarizes information about protein oligomerization and modulation of this process, demonstrating the role of oligomerization in oncogenesis by tumor suppressor protein p53, which forms tetrameric structure. Today, many studies focus on finding compounds that stabilize its tetramers. Among the methods for studying oligomerization, we present hydrogen/ deuterium exchange method coupled with mass spectrometry which is suitable for the detection of protein-protein interaction and analysis of oligomerization dynamics.
Keywords: karcinogeneze; Humans; hmotnostní spektrometrie; multimerizace proteinu; Deuterium Exchange Measurement; vodík-deuteriová výměna; Mass Spectrometry; lidé; Carcinogenesis; Tumor Suppressor Protein p53; Drug Design; Protein Multimerization; nádorový supresorový protein p53; racionální návrh léčiv